Rhodococcus enclensis sp nov., a novel member of the genus rhodococcus - Dastager, Syed Gulam; Mawlankar, Rahul R.; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2014)
A novel actinobacterial strain, designated, NIO-1009(T), was isolated from a marine sediment sample collected from Chorao Island, Goa, India. Phylogenetic analysis comparisons based on 16S rRNA gene sequences between strain MO-1009(T) and other members of the genus Rhodococcus revealed that strain NI0-1009(T) had the closest sequence similarity to Rhodococcus kroppenstedtii DSM 44908(T) and Rhodococcus corynebacterioides DSM 20151(T) with 99.2 and 99.1%, respectively. Furthermore, DNA-DNA hybridization results showed that R. kroppenstedtii DSM 44908(T) and R. corynebacterioides DSM 20151(T) were 39.5 (3.0%) and 41.7 (2.0%) with strain NIO-1009(T), respectively, which were well below the 70% limit for any novel species proposal. Phylogenetically strain NIO-1009(T) forms a stable clade with and R. kroppenstedtii DSM 44908(T) and R. corynebacterioides DSM 201511 with 100% bootstrap values. Strain NI-1009(T) contained meso-diaminopimelic acid as the diagnostic diamino acid and galactose and arabinose as the cell wall sugars. The major fatty acids were C-16:0, C-18:1 omega 9c, C-16:1(omega 6C and/or omega 7c) and 10-methyl C-18:0. The only menaquinone detected was MK-8(H-2), while the major polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannoside and one unknown phospholipid. The G + C content of the genomic DNA was 66.9 molok. The phenotypic and genotypic data showed that strain NIO-1009(T) warrants recognition as a novel species of the genus Rhodococcus for which the name Rhodococcus enclensis sp. nov., is proposed; the type strain is NIO-1009(T) (=NCIM 5452(T)=DSM 45688(T)).

Reclassification of bacillus isronensis shivaji et al. 2009 as solibacillus isronensis comb. nov and emended description of genus solibacillus krishnamurthi et al. 2009 - Mual, Poonam; Singh, Nitin Kumar; Verma, Ashish; Schumann, Peter; Krishnamurthi, Srinivasan; Dastager, Syed Gulam; Mayilraj, Shanmugam (International Journal of Systematic and Evolutionary Microbiology, 2016)
An investigation into the taxonomic position of Bacillus isronensis MTCC 7902(T) revealed that the strain shares a common phylogenetic lineage with Solibacillus silvestris MTCC 10789(T). It displays considerable overlap in phenotypic properties with the genus Solibacillus, including endospore shape and position, oxidase and catalase activities, presence of iso-C-15 : 0, C-16 : (1)omega 7c alcohol and iso-C-17 : 1 omega 7c as major cellular fatty acids, A4 alpha-type cell-wall peptidoglycan, polar lipids and menaquinone pattern. These features reinforce the findings of molecular phylogenetic analyses based on 16S rRNA gene, gyrB gene and 16S-23S internal transcribed spacer (ITS) region sequences and, in line with the recommendations of Kampfer et al. [Int J Syst Evol Microbiol 56 (2006), 781-786], provide justification for the transfer of Bacillus isronensis from the genus Bacillus to Solibacillus as Solibacillus isronensis comb. nov. The type strain is B3W22(T) (=MTCC 7902(T) =DSM 21046(T) =JCM 13838(T)). An emended description of the genus Solibacillus is also provided.